Performance management on the shop floor – an investigation of KPI perception among managers and employees. Issue 4 (24th July 2020) - Ohlig, Jasmin; Hellebrandt, Thomas; Metzmacher, Amelie I.; Pötters, Patrick; Heine, Ina; Schmitt, Robert H.; Leyendecker, Bert
Abstract : Purpose: The purpose of this paper is to investigate the application of key performance indicators (KPIs) on shop floor level in German small- and medium-sized enterprises (SMEs). The paper focuses on the examination of perception differences between shop floor employees and managers with regard to collection, calculation and consolidation of KPIs as well as visualization and motivational aspects. Design/methodology/approach: To examine the hypothesis on differing perceptions regarding KPIs, 27 qualitative interviews with shop floor employees and production managers within 6 SMEs from the German machinery and equipment industry were conducted on basis of a semi-structured guideline. Findings: The findings show that shop floor employees self-assess a lack of relevant knowledge when it comes to understanding KPIs. Moreover, the results show that shop floor employees perceive the visualization of shop floor KPIs as insufficient and non-motivational. This goes along with the finding that managers are aware of the lacking benefit of KPIs resulting from the rather negative perception of shop floor employees. The interviewed managers recognize a strong potential for improvement of their KPI systems. Originality/value: The interview results confirm the need to design a performance management system on the shop floor that considers and aligns both management and operations, is directed to the shop floor level, considers explicitly the perspective of employees and integrates motivational elements.